PENINGKATAN KOGNITIF SISWA DALAM MEMAHAMI SURAH AL-INSYIRAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) DI KELAS IX-C SMPN 1 SIDIKALANG - Nursiah Bancin (Universitas Negeri Medan, 2018)
Abstract: Student Civnitive Improvement In Understanding The Surah Al-Insyirah Through Cooperative Learning Model Type Student Team Achievement Divisions (STAD) In Class IX-C SMPN 1 Sidikalang. The research was conducted with two cycles by applying cooperative learning model of Student Team Achievement Divisions (STAD). The application of STAD type cooperative learning model is done in an effort to increase activity and student learning outcomes in the field of study of PAI. Research subjects are all students of class IX-C SMP Negeri 1 Sidikalang which amounted to 12 students who are Muslim. The result of the research shows ; Student Teams Achievement Division cooperative learning model can improve students' cognitive especially surah al-insyirah material, that is on the first cycle average score of 60 test with 25% learning completeness and on cycle II average test score 83.3 with learning completeness up to 91%.Keywords: STAD Cooperative Learning Model, Learning Activity, Learning Outcomes.Abstrak: Peningkatan Kognitif Siswa dalam Memahami Surah Al-Insyirah melalui Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions (STAD) di Kelas IX-C SMPN 1 Sidikalang. Penelitian dilakukan dengan dua siklus dengan menerapkan model pembelajaran kooperatif tipe Student Team Achievement Divisions (STAD). Adapun penerapan model pembelajaran kooperatif tipe STAD dilakukan dalam upaya meningkatkan aktivitas dan hasil belajar siswa pada bidang studi PAI. Subjek penelitian adalah seluruh siswa kelas IX-C SMP Negeri 1 Sidikalang yang berjumlah 12 siswa yang beragama islam. Hasil penelitian menunjukkan ; Model pembelajaran kooperatif tipe Student Teams Achievement Division dapat meningkatkan kognitif siswa khususnya materi surah al-insyirah, yakni pada siklus I rata-rata nilai tes 60 dengan ketuntasan pembelajaran sebesar 25% dan pada siklus II rata-rata nilai tes 83,3 dengan ketuntasan pembelajaran naik menjadi 91%.Kata Kunci : Model Pembelajaran Kooperatif STAD, Aktivitas Belajar, Hasil Belajar.